Dampak Shooting Three Point Plyometric dan Ladder terhadap Hasil Shooting Three Point Bola Basket - Argian Rizki Taufik; Amung Ma’mun; Mulyana Mulyana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to determine the impact of three point plyometric and ladder shooting impacts on Bola basket three point shooting results. The research method used was experiment. The research was used group pretest-posttest designs. The population was extracurricular students of SMAN 9 Bandung were of 20 participants. 10 participants in the three point plyometric shooting group, 10 participants in the three point ladder shooting group, samples were taken by purposive sampling technique. The instrument used was a three-point shooting test for one minute through the treatment of 18 meetings. Analysis of research was used normality test, homogeneity test, paired sample t-test and independent sample-test. In conclusion, three point plyometric shooting exercises have a significant effect compared to three point ladder shooting exercises on the improved of three point shooting results. Keywords: Basketball, Ladder, Plyometric Shooting Three Point